2004
DOI: 10.1074/jbc.m406288200
|View full text |Cite
|
Sign up to set email alerts
|

PetC1 Is the Major Rieske Iron-Sulfur Protein in the Cytochrome b6f Complex of Synechocystis sp. PCC 6803

Abstract: Many of the completely sequenced cyanobacterial genomes contain a gene family that encodes for putative Rieske iron-sulfur proteins. The Rieske protein is one of the large subunits of the cytochrome bc-type complexes involved in respiratory and photosynthetic electron transfer. In contrast to all other subunits of this complex that are encoded by single genes, the genome of the cyanobacterium Synechocystis PCC 6803 contains three petC genes, all encoding potential Rieske subunits. Most interestingly, any of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 44 publications
3
38
0
Order By: Relevance
“…2A): whereas CydA was essentially undetectable by immunoblot analysis in WT, ⌬petC2, and ⌬petC3 strains, its expression was dramatically increased in the ⌬petC1 strain. This is in good agreement with earlier observations of a significantly increased cytochrome-bd oxidase activity in the ⌬petC1 strain (40). Most likely, due to cytochrome b 6 f complex deficiency in the ⌬petC1 strain, cytochrome-bd oxidase has to partly take over the role of the cytochrome b 6 f complex in PQH 2 re-oxidation to keep electron transport and energy transduction efficient, i.e.…”
Section: Pigment and Proteinsupporting
confidence: 92%
See 4 more Smart Citations
“…2A): whereas CydA was essentially undetectable by immunoblot analysis in WT, ⌬petC2, and ⌬petC3 strains, its expression was dramatically increased in the ⌬petC1 strain. This is in good agreement with earlier observations of a significantly increased cytochrome-bd oxidase activity in the ⌬petC1 strain (40). Most likely, due to cytochrome b 6 f complex deficiency in the ⌬petC1 strain, cytochrome-bd oxidase has to partly take over the role of the cytochrome b 6 f complex in PQH 2 re-oxidation to keep electron transport and energy transduction efficient, i.e.…”
Section: Pigment and Proteinsupporting
confidence: 92%
“…Usually, the construction of knock-out strains is a highly valuable standard method to elucidate the potential in vivo function of such proteins. The generation of ⌬petC Synechocystis strains has been reported recently (40), and it has already been shown that electron transfer is modified at least in the ⌬petC1 strain and that PetC2 can partly replace the major Rieske protein PetC1. However, it is unknown whether the absence of PetC1 (or the other PetC isoforms) influences pigment compositions in the cells or affects the expression, accumulation, or stability of the cytochrome b 6 f complex.…”
Section: Pigment and Proteinmentioning
confidence: 93%
See 3 more Smart Citations